Aggregation-induced delayed fluorescence luminogens: the innovation of purely organic emitters for aqueous electrochemiluminescence. Issue 40 (17th September 2021) - Zhang, Baohua; Kong, Yi; Liu, Huijun; Chen, Bin; Zhao, Bolin; Luo, Yelin; Chen, Lijuan; Zhang, Yuwei; Han, Dongxue; Zhao, Zujin; Tang, Ben Zhong; Niu, Li
Abstract : Electrochemiluminescence (ECL) using an aggregation-induced delayed fluorescence (AIDF) organic luminogen, i.e. AIDF-ECL, was reported for the first time, featuring "lighting" dark triplets ( ca. 75% in total) for all-exciton-harvesting ECL applications. Abstract : Due to overcoming the limitation of aggregation caused quenching (ACQ) of solid-state emitters, aggregation-induced emission (AIE) organic luminogens have become a promising candidate in aqueous electrochemiluminescence (ECL). However, restricted by the physical nature of fluorescence, current organic AIE luminogen-based ECL (AIECL) faces the bottleneck of low ECL efficiency. Here, we propose to construct de novo aqueous ECL based on aggregation-induced delayed fluorescence (AIDF) luminogens, called AIDF-ECL. Compared with the previous organic AIE luminogens, purely organic AIDF luminogens integrate the superiorities of both AIE and the utilization of dark triplets via thermal-activated spin up-conversion properties, thereby possessing the capability of close-to-unity exciton utilization for ECL. The results show that the ECL characteristics using AIDF luminogens are directly related to their AIDF properties. Compared with an AIECL control sample based on a tetraphenylethylene AIE moiety, the ECL efficiency of our AIDF-ECL model system is improved by 5.4 times, confirming the excellent effectiveness of this innovative strategy.